Characteristics of the Fourth Wave of Russian-Speaking Migration to the Czech Republic: Transnational Approaches, Belonging, and Identity Strategies - Stěpanova, Světlana (Lidé města, 2025)
This study focuses on the internal transformations of identity and belonging within the Russian-speaking migrant community in the Czech Republic, with particular emphasis on the case of the vocal ensemble “Russian Soul.” Drawing on theoretical frameworks of transnationalism (Basch, Glick Schiller, Blanc 1994), mobile identity (Vertovec 2009), translocational positionality (Anthias 2006), and hybrid subjectivity (Hall 1995), the author explores how everyday cultural practices, internal competition, and external political conditions shape identity strategies in a migration context. Methodologically, the article adopts a mixed-methods approach, combining analysis of online communication, a questionnaire survey with 61 respondents, and autoethnographic observation within a cultural collective founded by the researcher herself. This design allows for the identification of subtle shifts in systems of loyalty, symbolic boundaries, and mechanisms of cultural capitalisation that often remain overlooked. Special attention is given to the fragmentation of the ensemble as a symptom of broader diasporic dynamics – where collective belonging gives way to individual positioning strategies. The case illustrates how culture can shift from a vehicle of solidarity to a space of negotiation, and how identity becomes a flexible resource under conditions of institutional uncertainty. This article contributes to the study of Russian-speaking migration in Central Europe by offering empirical insight into the everyday identity dynamics of small cultural initiatives.